Anguilla bicolor McClelland 1844 - Esmaeili, Hamid Reza; Hamidan, Neshat (Zenodo, 2023)
2. Anguilla bicolor McClelland, 1844 ―Shortfin Eel― Native Taxonomy. Original description: Anguilla bicolor McClelland, 1844:178, 202, 209, Pl. 6 (fig. 1) [Sandoway, Malay coast, India; Syntypes: SMF 776 (1)]. Synonyms: Anguilla amblodon Günther, 1867; Anguilla bleekeri Kaup, 1856; Anguilla cantori Kaup, 1856; Anguilla dussumieri Kaup 1856; Anguilla foochowensis Chu & Jin, 1984; Muraena halmaherensis Bleeker, 1863; Muraena macrocephala Rapp, 1849; Anguilla malabarica Kaup, 1856; Anguilla malgumora Kaup, 1856; Anguilla moa Bleeker, 1849; Anguilla mowa Bleeker, 1852; Anguilla sidat Bleeker, 1852; Anguilla spengeli Weber, 1912. Status in the Arabian Peninsula. First report from the Arabian Peninsula by Attaala & Salim Rubaia (2005); confirmed by Freyhof et al . (2020:113). General distribution and Habitat. Indo-West Pacific: Seychelles, Mayotte (France), Madagascar and Mascarenes (La Réunion, Mauritius, Rodrigues) east to China and New Britain (Papua New Guinea), south to northern Western Australia. Freshwater, brackish, marine. Distribution in the Arabian Peninsula. Recorded from Yemen along the Arabian Sea and Gulf of Aden including Socotra archipelago (Attaala & Salim Rubaia 2005; Freyhof et al. 2020; Zajonz 2020). Economic importance. No commercial importance. Conservation. Near Threatened (NT). Remarks. Sometimes split into two subpopulations and listed as the subspecies A. bicolor bicolor in Western Indian Ocean, from East Africa to western Indonesia, and as A. bicolor pacifica in the western Pacific, from Indonesia to China and New Guinea (Heemstra et al. 2022). Fricke et al. (2023) considered Anguilla pacifica Schmidt, 1928 as distinct species. Published as part of Esmaeili, Hamid Reza & Hamidan, Neshat, 2023, Inland fishes of the Arabian Peninsula: Review and a revised checklist, pp. 201-226 in Zootaxa 5330 (2) on page 206, DOI:10.11646/zootaxa.5330.2.2, http://zenodo.org/record/8249316